Pengaruh Latihan Fisik Terhadap Kecepatan Lari Jarak Pendek dan Motivasi Belajar Siswa Kelas V SDN 005 Palas - Anugrah Fitra Ramadhan (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to determine the effect of structured physical exercise on short-distance running speed and learning motivation among fifth-grade students at SDN 005 Palas. A quantitative approach with a quasi-experimental method was employed using a one-group pretest-posttest design. The subjects were 18 fifth-grade students. Structured and continuous physical exercise was implemented as the intervention. Data were collected through short-distance running speed tests and a learning motivation questionnaire administered at both pre-test and post-test stages, then analyzed using statistical tests. The findings revealed that physical exercise significantly increased both short-distance running speed and student learning motivation. The intervention effectively addressed initial observations of low fitness levels and lack of enthusiasm for physical activities among students. The research innovatively examines the dual impact of a single structured exercise program on both a specific physical competency (running speed) and a psychological construct (learning motivation) within elementary physical education. Physical education teachers should integrate structured, continuous exercise programs as a dual-purpose strategy for enhancing both students' physical fitness and their motivational engagement in learning activities. The study contributes empirical evidence to physical education pedagogy, demonstrating that well-designed exercise interventions can simultaneously yield physiological and psychological benefits, supporting holistic student development.